Scientometric analysis of research on deliberate biosecurity threats reveals North-Transatlantic dominance - Suryesh Kumar Namdeo; GN Chandan (Journal of Biosafety and Biosecurity)
Academic research is crucial to understanding and preparing for the fight against deliberate biological threats; yet, existing efforts have been fragmented, necessitating a more comprehensive examination of the field’s evolution. This study presents a scientometric analysis of deliberate biosecurity threats over the last 20 years, focusing on publication patterns, collaboration dynamics, research priorities, and leading publication venues. We analyzed 791 articles published between 2004 and 2023 using the Web of Science and Scopus databases. Results indicate a notable increase in publications dominated by North-Transatlantic countries, particularly the United States and the United Kingdom, which prioritize such areas as dual-use technology, synthetic biology, and virus-related biosecurity challenges. A comparative analysis of G7 and BRICS collaborations underscores substantial disparities in research output, with the G7 leading in international biosecurity research collaborations. Furthermore, the study reveals limited biosecurity research and collaboration in the Global South. Therefore, we encourage further exploration of biosecurity research to promote inclusive and collaborative global efforts. This study provides valuable insights for researchers and policymakers regarding biosecurity research priorities related to deliberate threats, and it highlights the need to address global disparities.